(Im)pessoalidade numérica : registro na pele - Vanzin, Nicole Martinato (My University, 2018)
?(Im)pessoalidade numérica: Registro na pele? consists in a creation of as only and new numeration to each person parto of a society. This purpouse is reaction to the stipulated way of numeration that Brazil lie nowadays, where we are represented by a lot of different numbers. The artist substantiated this ideas using concepts of BodyArt, Performance and Artist Installation. Creating an only identification number is possible to value at the same time the individual and collective equally. This project consists of a video performance which the artist tatooed on her arm her new numerical identification. With the video will have a installation of a new identification cards printed in glass and mounted in vertical line. When viewed at the front the images and numbers mixed, representing the collective, however with the movement of the observer to the sides, it is possible to see each person and new identification number, representing their singulaties (sic).
O trabalho ?(Im)pessoalidade numérica: Registro na pele? consiste na criação de uma nova e única numeração para cada indivíduo. É uma reação a forma de identificação estipulada atualmente no Brasil, onde somos muitos e diferentes números. Para fundamentar essas ideias a artista utilizou conceitos de BodyArt, Performance e Instalação. A proposta é criar um único número para identificar cada cidadão, adequando-se assim à realidade numérica, mas valorizando a individualidade de cada um. O trabalho é composto por uma vídeo performance em que a artista tatuou em seu braço sua nova identificação numérica. Juntamente com o vídeo terá uma instalação de novas carteiras de identificação impressas em vidro e montadas em fila indiana. Quando vistas de frente as imagens e números misturam-se, representando o coletivo, entretanto, com o deslocamento do observador para as laterais, é possível visualizar cada pessoa com seu novo número de identificação, representando suas singularidades (sic).
Keywords: Performance (Arte); Tatuagem; Identidade; Individualidade